"Exploring sunken ruinous roads": the First World War poet as archaeologist. Issue 1 (2nd January 2016) - Lowe, Peter
ABSTRACT: This paper examines some of the poetry of the First World War's aftermath and suggests that the process by which poets revisited their wartime experiences often resulted in poetry that was uneasily aware of its ability to offer only a partial alleviation of the traumas that it drew upon. Using the metaphor of archaeology as a way of approaching this practice, the essay considers whether the activity of "excavating" and writing about the past held out, for the generation of soldier-poets, the possibility of finding psychological equilibrium as memories were uncovered, claimed and brought to the surface. Articulating experience through poetry revives it and simultaneously imbues it with traces of form and structure; suggesting a degree of understanding on the part of a poet coming to terms with "unthinkable" things, but at the same time it is not without considerable risk for the excavating poet-archaeologist, who is uncomfortably woven into the memories that he probes.